1999
DOI: 10.1023/a:1009870524359
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This review provides an historical perspective on events that have shaped our pathophysiological understanding of sepsis during this century and, as a result, have in_uenced the design of glucocorticoid treatment trials. A structured format to evaluate clinical investigation of glucocorticoid treatment in patients with sepsis is presented. From the early 1950s to the late 1980s, the methodological quality of randomized trials improved, while the science dictating the design of treatment protocols overlooked pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(7 citation statements)
references
References 116 publications
0
5
0
2
Order By: Relevance
“…The response to hydrocortisone treatment observed in the present study and in other randomized trials of patients with septic shock [28,[38][39][40][41] and severe pneumocystis pneumonia [42] contrasts with the negative findings of older trials. These negative finding may be related to the short duration of treatment [14,15]. Among a number of studies in support of this hypothesis [14], a randomized trial of patients with severe CAP found that a single dose of hydrocortisone (10 mg/kg) before antibiotic administration showed no effect on plasma TNFlevels [43].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The response to hydrocortisone treatment observed in the present study and in other randomized trials of patients with septic shock [28,[38][39][40][41] and severe pneumocystis pneumonia [42] contrasts with the negative findings of older trials. These negative finding may be related to the short duration of treatment [14,15]. Among a number of studies in support of this hypothesis [14], a randomized trial of patients with severe CAP found that a single dose of hydrocortisone (10 mg/kg) before antibiotic administration showed no effect on plasma TNFlevels [43].…”
Section: Discussionmentioning
confidence: 99%
“…These negative finding may be related to the short duration of treatment [14,15]. Among a number of studies in support of this hypothesis [14], a randomized trial of patients with severe CAP found that a single dose of hydrocortisone (10 mg/kg) before antibiotic administration showed no effect on plasma TNFlevels [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many variables to consider, including the type of GC to be used, timing, dosage, mode of delivery, co-interventions, duration, and tapering. Over the last 40 years, multiple randomized trials investigating GC treatment in critical illness have clearly shown that the design of a treatment protocol has a profound impact on treatment response and outcome (304,305). The CONSORT (306) and GRADE (307) systems, while useful in evaluating the quality of a randomized trial, unfortunately lack a position on two fundamental elements of a trial design, namely the disease pathophysiology and the pharmacological principles applicable to the investigated drug.…”
Section: Conclusion and Implications For Glucocorticoid Treatmentmentioning
confidence: 99%
“…El papel fundamental de los esteroides en la sepsis se consideró originalmente con base en su perfil farmacodinámico como inmunosupresores y antiinflamatorios. 98 La dosificación y la duración de la terapia han sido motivo de muchos estudios, y con base en sus resultados hay varios elementos para resaltar:…”
Section: Esteroides Esteroides Esteroides Esteroides Esteroidesunclassified